2005
DOI: 10.1007/s10661-005-7061-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of heavy metals in Penaeus Semisulcatus from Persian Gulf and possible role of metallothionein in their redistribution during storage

Abstract: The study was conducted between January and December 2002. The main objective of this study was evaluation of effects of refrigerated storage duration on redistribution of three trace elements (Cd, Cu and Zn) in tissues (exoskeleton, abdominal muscle and hepatopancreas) of a shrimp species (Penaeus semisulcatus). Moreover, the possible roles of metallothionein (a kind of metalloprotein) in redistribution of the elements in tissues of the selected species were assessed. The specimens were sampled from northwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 59 publications
2
18
0
4
Order By: Relevance
“…It appears to have a protective effect against the toxicities of both cadmium and lead [15] [16]. Hence, the relatively high levels of these metals comparing to other metals studied can be attributed to their essentiality [17]. The levels of Zn in gills of Anthias squamipinnis, Snubnose emperor, Dicentrarchus labrax and Lutjanus ehrenbergii were also higher than the other species studied ( Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…It appears to have a protective effect against the toxicities of both cadmium and lead [15] [16]. Hence, the relatively high levels of these metals comparing to other metals studied can be attributed to their essentiality [17]. The levels of Zn in gills of Anthias squamipinnis, Snubnose emperor, Dicentrarchus labrax and Lutjanus ehrenbergii were also higher than the other species studied ( Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…In the present study also, on comparing the metals concentration in the fish and shrimp species it can be easily conjectured that irrespective of the locations, the shrimps accumulated more metals than the fish species. Shrimps are benthic organisms that feed by stirring the sediment up and collecting very small particles of organic matter, and so they would be exposed to the metals bound to this food (FSA 2005;Pourang et al 2005).…”
Section: Distribution Of Metals In Fish and Shrimpmentioning
confidence: 99%
“…Fe and Cu is also an essential trace element for animal metabolism. It was reported that Zn, Fe, and Cu are the most abundant elements in the muscle followed by other metals [15][16]. Therefore, it could be explained that the slightly high levels of these metals are necessary for biological functions of organisms.…”
Section: Resultsmentioning
confidence: 99%